Pengaruh Kepuasan Kerja Karyawan Terhadap Turnover Intentions Dengan Withdrawal Cognitions Dan Job Search Sebagai Variabel Pemediasi - Sihombing, Agus; Saragih, Susanti (Business and Management Review, 2012)
The purpose of this research is to  examine the effects of job satisfaction and job search on turnover intentions in which withdrawal cognitions as mediating variable.  Variables in this research were measured via a survey of 95 administration staffs of credit banking company in Bandung, West Java. Path analysis model were used to examine the significant level and the direct effects of job satisfaction on turnover intentions and also indirect effects of job satisfaction on turnover intention, withdrawal cognitions and job search as mediating variables.  Results showed that job satisfaction significantly influences turnover intentions and job satisfaction significantly influences withdrawal cognitions. In addition, this research found that withdrawal cognitions found significantly mediated the relationship between job satisfaction and job search. Job satisfaction is also found significantly influences job search and job search significantly found mediated the relationship between job satisfaction and turnover intentions. Keywords:  Job Satisfaction, Withdrawal Cognitions, Job Search, Turnover Intentions, Mediating Variable